2001
DOI: 10.1177/147323000102900404
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation of New Autologous Biomaterials into Jaw Cleft

Abstract: This study compared bone-marrow grafting using chondroid or fibula bone grafts transplanted into simulated alveolar bone defects in mice. The osteogenic procedure was also investigated. As an experimental model of the maxillary alveolar bone cleft, suitable for testing bone-inductive materials, a surgical trephine with a low-speed dental engine was used to form critical-sized defects in the pre-maxillary bones of male mice. Distraction osteogenesis was performed using an external fixation device. The osteotomy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…They obtained an external callus comprising hyaline cartilage by tibial distraction osteogenesis with an external fixator and implanted it into the defects. They found that the external callus had bone formation and remodeling in its interior and promoted bone adhesion [157].…”
Section: Maxillary Drilling Modelmentioning
confidence: 99%
“…They obtained an external callus comprising hyaline cartilage by tibial distraction osteogenesis with an external fixator and implanted it into the defects. They found that the external callus had bone formation and remodeling in its interior and promoted bone adhesion [157].…”
Section: Maxillary Drilling Modelmentioning
confidence: 99%
“…The main method of midfacial reconstruction has been the use of orthognathic surgery or osteotemy distraction osteogenesis (ODO) (Kawata et al, 2001; Zhao et al, 2011). Although good aesthetic results have been reported even without bone grafting, these methods can deprive patients of proper restoration of the maxillomandibular dentition due to extensive fibrosis, serious bleeding, and increased incidence of resistant postoperative infection (Ayoub et al, 2001; Elsalanty et al, 2009).…”
mentioning
confidence: 99%